2017
DOI: 10.22606/jan.2017.21001
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Catalyst Structure and Mechanism in Methanol Synthesis

Abstract: Abstract. Methanol synthesis is a mature industrial process, where industrial Cu/ZnO/Al 2 O 3 catalyst is commonly used. Howerver, function of the active catalyst component and reaction mechanism is still vague. In this contribution, the function of each catalyst component including the synergy between Cu and ZnO, reaction mechanism including carbon source of methanol, key intermediates and elementary steps, and kinetics of methanol synthesis and impurities formation are discussed based on the latest literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Additionally, a similar synergy between heteroatoms in bimetallic phosphides was observed in Co–Ni and Fe–Ni bimetallic phosphides, where a different metal composition enhanced the HDS activity through modification of the active sites. Recent studies have also shown that a Ru 1 Mo 1 P bimetallic catalyst results in a strong promotional effect for the selective hydrogenation of substituted aromatic hydrocarbons. , For furfural hydrogenation, the synergistic effect in Ru 1 Mo 1 P increases the adsorption energy of the carbonyl O on surface active sites and accelerates hydrogenation of furfural to furfural alcohol . Similarly, this interaction may be important for methanol synthesis, as CO 2 must adsorb on surface active sites and hydrogenate to form methanol. ,,,, Therefore, the adsorption strength of CO may improve activation of CO 2 , stabilize CO species, and facilitate the hydrogenation steps toward methanol. , …”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Additionally, a similar synergy between heteroatoms in bimetallic phosphides was observed in Co–Ni and Fe–Ni bimetallic phosphides, where a different metal composition enhanced the HDS activity through modification of the active sites. Recent studies have also shown that a Ru 1 Mo 1 P bimetallic catalyst results in a strong promotional effect for the selective hydrogenation of substituted aromatic hydrocarbons. , For furfural hydrogenation, the synergistic effect in Ru 1 Mo 1 P increases the adsorption energy of the carbonyl O on surface active sites and accelerates hydrogenation of furfural to furfural alcohol . Similarly, this interaction may be important for methanol synthesis, as CO 2 must adsorb on surface active sites and hydrogenate to form methanol. ,,,, Therefore, the adsorption strength of CO may improve activation of CO 2 , stabilize CO species, and facilitate the hydrogenation steps toward methanol. , …”
Section: Introductionmentioning
confidence: 75%
“…49 Similarly, this interaction may be important for methanol synthesis, as CO 2 must adsorb on surface active sites and hydrogenate to form methanol. 5,6,11,50,51 Therefore, the adsorption strength of CO may improve activation of CO 2 , stabilize CO species, and facilitate the hydrogenation steps toward methanol. 52,53 Therefore, in this study, we investigated Ru X Mo (2−X) P (X = 0.8, 1.0, 1.2) catalysts for CO 2 hydrogenation to determine (1) if the methanol production rate of MoP can be enhanced through incorporation of Ru, (2) how the composition of the Ru−Mo phosphide affects methanol production rates, and (3) if and how the CO 2 binding sites change with the formation of a bimetallic Ru−Mo phosphide.…”
Section: Introductionmentioning
confidence: 99%
“…An In 2 O 3 /ZrO 2 catalyst 287 300 highlighting the strong positive effect of the pressure on the thermodynamics and kinetics of the reaction. Three main pathways 301 have been proposed for CO 2 hydrogenation to methanol (Fig. 6), with a mechanism slightly different from the one represented in Fig.…”
Section: Catalysis Science and Technology Mini Reviewmentioning
confidence: 99%
“…Three main pathways 301 have been proposed for CO 2 hydrogenation to methanol ( Fig. 6 ), with a mechanism slightly different from the one represented in Fig.…”
Section: Materials and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation